Diálogos e tensões: o olhar de professoras negras e brancas sobre a constituição da identidade negra no contexto escolar - Constantino, Francisca de Lima (2014)
In this research, entitled Dialogues and tensions: the perception of black and white teachers about the formation of black identity in the school context, we seek to understand, from the dialogue between black and white teachers, what knowledge can be identified and created for ways to strengthen the identity of black children in schools? Ergo, the following objectives are delineated: to discuss and reach consensus with teachers about a concept of identity for promoting the positive development of black identity; and with the teachers, analyze the practices, materials and/or training courses that can strengthen the identity of black children; also, suggest and elaborate practices that strengthen black identity, and point out ways to promote the education of racial and ethnic relations. The research objectives were achieved based on a theoretical study, followed by a field study. The former included readings about the education of racial and ethnic relations; the concepts of identity, diversity and respect for differences; equality of differences and their relation to a dialogic approach and anti-racist education. To understand the concept of identity, the main references used were: Giddens; Gomes; Munanga and Castells; and the relationship between black identity and school was based on the theorists of sociology, anthropology and education. Our investigations were also based on researchers from the Centre of Research on Theories and Practices for Overcoming Inequalities (CREA) and the Center of Research on Social and Education Action (NIASE), which help in the understanding of a dialogical education and equality of differences. To investigate what has been produced in Brazil about this theme, a production review was conducted in SciELO, as well as in some WG of ANPED. The field study was characterized by monitoring discussion groups comprised of six elementary school teachers (4 black and 2 white teachers), which developed dialogic practices in their classes. The research developed was based on the critical communicative methodology, which involves an intersubjective dialogue between participants and researcher, with the subjects critical self-reflection. There were 5 communicative groups, which enabled the participants to dialogue about topics previously agreed on regarding the research question. As for the results, we can state that it is possible to strengthen black identity by means of intentional teaching practices that are committed to and guided by knowledge. For this, one must resort to valuing ethnic and racial diversity, being open to dialogue and promoting actions to promote the equality of differences. From the discussion groups, we concluded that conceiving a positive black identity in the school context requires a black presence in the school, in other words, one must have the history, culture and black ancestry in the school environment and break the silence that still exists about being black. We also conclude that the practices to affirm black identity must be participatory, which means that in addition to narrating stories about Africa and black Brazilians and recounting these activities, it is fundamental having the presence of blacks, Africans and indigenous people in the school context, in order to help black and white children do away with the stereotypes inserted in our society. Another element to be highlighted in terms of teaching practices in the discussion of valuing diversity, regards teacher training courses; such courses are seen as indispensable for understanding the issue presented herein. Finally, we conclude that there is still much to be overcome when we deliberate on the equality of differences and Brazilian racism. Black identity exhibits an inner complexity that requires further studies by researchers and more sensitivity by the teachers. This issue does not end here, with questions that remain open for discussions in future studies.